2014
DOI: 10.5511/plantbiotechnology.14.1021a
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiles of nodule senescence in <i>Lotus japonicus</i> and <i>Mesorhizobium loti</i> symbiosis

Abstract: Nodule senescence is a complex developmental process during which essential nutrients are recycled. In order to understand the regulatory mechanism, transcript-profiling analysis during nodule senescence was performed in the Lotus japonicus-Mesorhizobium loti symbiosis. Microarray data showed significantly up-regulated expressions in 641 genes out of a total of 20,165 genes during nodule senescence, and down-regulated expressions were observed in 416 genes. These up-regulated genes during senescence were relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…a–d). These results are in agreement with previous reports suggesting that elevation of proteolytic activity during nodule senescence results in nodule protein and lb degradation (Pladys & Vance, ; Chungopast et al ., ). It seems logical to propose that the nutrients obtained from the protein degradation are recycled and used as a nitrogen source to sustain plant growth.…”
Section: Discussionmentioning
confidence: 97%
“…a–d). These results are in agreement with previous reports suggesting that elevation of proteolytic activity during nodule senescence results in nodule protein and lb degradation (Pladys & Vance, ; Chungopast et al ., ). It seems logical to propose that the nutrients obtained from the protein degradation are recycled and used as a nitrogen source to sustain plant growth.…”
Section: Discussionmentioning
confidence: 97%
“…Many researchers have performed transcriptome or RNA-seq analyses in L. japonicus and identified genes upregulated after M. loti infection (Chungopast et al 2014;Handa et al 2015;Kouchi et al 2004). From these data, we found that the Ljmybr transcription factor (chr4.CM0004.2240.r2.d) was up-regulated in roots after M. loti infection.…”
Section: Ljmybr Expression Analysis Using Quantitative Real-time Pcr mentioning
confidence: 61%
“…Previously, researchers performed transcriptome or RNA-seq analysis and identified many upregulated genes in Lotus japonicus nodules after Mesorhizobium loti infection (Chungopast et al 2014;Handa et al 2015;Kouchi et al 2004). From these data, we found one upregulated gene, MYB-related transcription factor (Ljmybr).…”
mentioning
confidence: 94%
“…We have reported that nodule senescence in the Ox1 line is delayed [33]. Quantification by qRT-PCR showed that the expression of all three nodule senescence marker genes (coding a heat shock protein, an osmotin precursor, and cysteine protease Cyp2; [33,49,50]) was increased in flooded nodules relative to untreated nodules of WT and 96642; the increase was much lower or absent in the nodules of Ox1 and Afx1 (Figure 3).…”
Section: Resultsmentioning
confidence: 99%